Jesus ‘the Just’ - Bockmuehl, Markus (Journal for the study of the New Testament, 2023)
While praise of the righteous is endemic in both Jewish and Christian Scripture, its application to named individuals is remarkably rare throughout. In the New Testament, it is reserved for pre-Christian saints and especially for Jesus himself—most clearly in Acts. Responding to the suggestion (by Richard Hays and others) that ‘the Just’ was specifically a messianic title, the article shows instead that its application to figures like James the brother of Jesus and Simon the son of Onias II documents part of a development toward the rabbinic usage of the Tzaddiq. The Just is a typically retrospective honorific designating a rare observant and pious person, possibly suffering and persecuted but divinely vindicated and endowed with charismatic qualities, who facilitates mediation between God and human beings and helps sustain the world.